Study of the Difference Between Centric Occlusion and Retruded Contact Position - Polasek, Antonia; Plisko, Manuela; Profozic, Anja; Plazibat, Antonia; Cimic, Samir (The Journal of Dentists, 2022)
Purpose: The aim of this study was to investigate the difference between retruded contact position (RCP) and centric occlusion (CO) at the level of mandibular condyles. Materials and methods: Study included 20 completely dentate participants (average 24.4 ± 1.2 years). All recordings of the condylar deviations were measured with the use of the ultrasound mandibular recording device with six degrees of freedom. CO was determined using active method of centric relation recording (participants were trained to stationary hinge and maintain the position of the lower jaw at the first tooth contact/contacts). RCP was determined with passive method of centric relation recording (chin point guidance). RCP and CO deviations to the reference position (habitual occlusion) were recorded with the use of the mandibular recording device at the level of x (anterior – posterior), y (vertical) and z (lateral) axes. Linear RCP and CO deviations (from the habitual occlusion) were measured. Descriptive statistics was measured, and the RCP and CO deviation values were compared using independent samples T test. Results: Average linear condylar deviation values for the CO were 1.30 ± 1.14 mm, and 2.13 ± 1.89 mm for the RCP. Independent samples T test showed statistically significant difference between RCP and CO linear deviation values (α=0.021). Conclusions: There is a difference in the positioning of the condyle within temporomandibular joint, with passive or active centric relation recording methods. CO and RCP can be identified as different occlusal positions.